The Role of Leadership through Structural Empowerment in Enhancing Healthcare Service Quality: A Systematic Literature Review - Mila Hestika Sari; Mira Triharini; Retnayu Pradanie (Universitas Pahlawan Tuanku Tambusai, 2026)
Healthcare service quality has become a critical issue due to its direct impact on patient safety, satisfaction, and organizational performance. Leadership has been identified as a key factor influencing healthcare service quality outcomes. This study aims to systematically review the role of leadership in improving healthcare service quality. This study employs a systematic literature review approach following PRISMA guidelines, utilizing databases including Scopus, PubMed, and Web of Science. Articles published between 2015 and 2025 were included based on predefined inclusion criteria, with most studies adopting a cross-sectional design. The findings indicate that leadership plays a fundamental role in enhancing healthcare service quality. Leadership demonstrates the strongest impact on improving patient care outcomes, employee engagement, and organizational performance. This study proposes a conceptual framework that can guide future research and practice. Furthermore, leadership significantly improves service quality through employee engagement, organizational culture, and innovation. Leadership also indirectly influences patient outcomes through mediating variables such as work engagement and structural empowerment. However, gaps remain in integrating leadership models with healthcare service quality frameworks.